The influence of psychological determinants and retirement planning on perceived bridge employment: examining the moderating effect of job satisfaction among employees in Sabah / Zaiton Osman - Osman, Zaiton (2015)
Retirement forces older workers to disconnect with their previous behavioural patterns and economic position. Transition and adjustment from working life to retirement places great psychological pressure and financial distress on older workers, especially those with dependent children. Bridge employment provides a solution for older workers to continue working after retirement while transitioning into retirement slowly and smoothly. As losing the job role has a significant impact on the psychological well-being of retirees, engaging in bridge employment helps to fulfil the important psychological functions of older workers by providing an adapt ive style to retirement. This study investigates the influence of psychological determinants (future time perspective, retirement goal clarity and financial knowledge) and retirement planning on bridge employment. Moreover this study also examines the moderating effect of job satisfaction among employees in Sabah. Retiring individuals must adapt and make major life transitions. A self-administered questionnaire was used in this study and a total of 523 samples were collected for nine major district in Sabah. Pearson Correlation and Multiple Linear Regression were conducted to determine the relationship between psychological determinants, retirement planning and perceived bridge employment. The findings from this study show a positive association between future time perspective and financial knowledge on bridge employment and a negative association between retirement goal clarity and retirement planning on bridge employment. Subsequently, job satisfaction was proven to moderate the relationship between psychological determinants, retirement planning and bridge employment. The study indicated that there is a need for aggressive promotion on financial knowledge, especially on retirement planning as well as programs on retirement preparedness (seminars, workshops, consultations, talks and surveys) in all organisations (government or private firms) as it will help to prepare employees for retirement and educate employees on other available retirement options such as bridge employment. Moreover, bridge employment opportunities should also be drafted for middle class income employees with a low level of education in both the government and private sectors, rather than just for highly educated employees only.